Anion exchange composite membrane based on ionic liquid-grafted covalent organic framework for fuel cells. (8th August 2022) - Zhang, Ningxin; Li, Ping; Li, Xuan; Tang, Shaokun
Abstract: Covalent organic frameworks (COFs) have been considered promising hydroxide-conducting materials for their highly ordered crystalline porous structure and tunable functionality. However, the lack of hydroxyl conduction functional groups on the COFs frameworks restricts their further development in anion exchange membrane fuel cells (AEMFCs). At present, impregnated ionic liquids (ILs) are mainly used to solve this problem, but they still face the challenge of ILs leakage under working conditions. Here, we report a novel IL-functionalized covalent organic framework (IL-COF), which is prepared by grafting guanidinium-based IL onto the channel walls of COF via the Williamson ether reaction and then doped into guanidinium-functionalized poly(2, 6-dimethyl-1, 4-phenylene oxide) (GPPO) to prepare IL-COF/GPPO composite membranes. The ILs grafted into the COFs nanochannels act as the "active sites" in the membranes to enhance the migration rate of the hydroxide ions and thus improve the conductivity. Accordingly, the hydroxide conductivity of the resultant IL-COF/GPPO composite membrane with IL-COF doping amount of 5 wt% can reach up to 89.93 mS cm −1 at 80 °C under hydrated condition, 61% higher than that of the pristine GPPO membrane. Meanwhile, its hydroxide conductivity retains 90.31% after alkaline treatment for 14 days. Compared with IL-impregnated COF composite membrane (IL@COF/GPPO), IL-COF/GPPO membrane has superior hydroxyl conductivity and long-term stability since chemical grafting can more firmly immobilize ILs into COF channels than impregnation. Graphical abstract: Image 1 Highlights: Guanidinium-based IL-grafted COF (IL-COF) is successfully prepared. IL-grafted COF is blended with GPPO to fabricate composite membrane. IL is fixed within COF channels by covalent linkage to form continuous ion channels. The hydroxide conductivity and mechanical properties are simultaneously enhanced. The IL-grafted COF-based AEM can effectively avoid leakage of functional groups.